A retrospective quality assessment of a hospital-based drug information service - Cruz, Marie Cicelie Jacobo
Quality assessment programs in drug information services have already been conducted in some countries where drug information centers exist such as the United States, Australia, India, Germany, Singapore, and Malaysia among others. In Manila, Philippines, there are four institutions providing drug information services, but none had undergone a formal quality assessment program. The objective of this study is to evaluate the quality of a hospital-based drug information service based on the structure-process-outcome model of quality assessment. Methods: A descriptive-evaluative study was used to retrospectively assess the quality of drug information services covering a period of three years (January 2006 to December 2008). Three evaluation instruments or tools were created, pilot-tested, and eventually employed to measure structure, process, and outcome parameters. The structure and process parameters employed secondary data obtained from the hospital drug information unit. For the outcome parameter, a survey was conducted among the previous users of the service using the outcome evaluation form. Results: The drug information service is under one of the divisions of the Pharmacy Department and has 12 pharmacists. Funded by the hospital, it operates on a 24-hour basis, mainly, for the purpose of providing support to clinical services, education, research and other specialized drug information services. Majority of the queries asked by nurses and most of the questions simply asked about the availability of the product. Requests were usually received by phone, answered in less than 5 minutes, and utilized primary tertiary literature. Process evaluation revealed very satisfactory rates. Majority of the information was used for patient care, specially, adverse drug reactions and enhancing therapeutic effectiveness, rather than for education or research. Requesters of drug information perceived professional quality, clarity, timeliness and helpfulness of the information as very good. Conclusion: The drug information services provided by the hospital pharmacy department is comparable to the published information on drug information services provided in other countries. However, certain areas still need improvement for better delivery of quality service. The creation of a separate unit for drug information, presence of full-time pharmacists, performance of all the steps in answering drug information requests and regular conduct of quality assessment programs must be established.